Identification and validation of a novel autophagy gene expression signature for human bladder cancer patients - Sanaa Eissa; Marwa Matboli; Nahla Awad; Yousif Kotb (Tumor Biology)
We sought to identify and validate a novel urinary autophagy transcript signature in patients with bladder cancer and evaluate its clinical utility. We performed an initial screening for seven autophagy transcript–based panel (autophagy-related protein 12 (ATG12); WD repeat domain, phosphoinositide interacting 2 (WIPI2); FYVE and coiled-coil domain-containing protein 1 (FYCO1); microtubule-associated protein light chain (MAPLC3); RB1-inducible coiled-coil 1 (RB1CC1); tachylectin-II-like beta-propeller domain 1 (TECPR1); and Unc-51-like kinase (ULK1)) that was identified based on bioinformatics analysis followed by SYBR Green–based polymerase chain reaction array validation in paired tissue and urine samples. Afterward, we evaluated the expression of differentially expressed autophagy transcripts in an independent validation set with reverse transcription quantitative real-time polymerase chain reaction in urine sediments of 140 patients with bladder cancer, 68 patients with benign urological lesions, and 74 healthy controls (age and sex matched). The expression levels of ATG12, FYCO1, TECPR1, and ULK1 in paired bladder tissue and urine samples were significantly lower in bladder cancer than in control group (p < 0.001). In the validation set, the receiver-operating characteristic curve analyses demonstrated that each urinary autophagy transcripts showed high sensitivity and specificity for distinguishing bladder cancer from non–bladder cancer patients (ATG12, 75.4% and 86.1%; FYCO1, 87% and 75.7%; ULK1, 85.5% and 75.6%; and TECPR1, 90% and 81.9%). We document and validate a novel autophagy transcript signature for human bladder cancer diagnosis: bilharzial and non-bilharzial types.